169k views
1 vote

(3)/(2) + (2m)/(9) = (37)/(18)

How do I solve this and make it the most simplified it can be?​

User Dan Erez
by
5.4k points

2 Answers

4 votes

Answer:


m = (5)/(2)

Explanation:


(3)/(2) + (2m)/(9) = (37)/(18)

Multiply through by 18 to eliminate the fraction

That's


18 * (3)/(2) + 18 * (2m)/(9) = 18 * (37)/(18) \\ 27 + 4m = 37

Subtract 27 from both sides

That's


27 - 27 + 4m = 37 - 27 \\ 4m = 10

Divide both sides by 4

That's


(4m)/(4) = (10)/(4)

We have the final answer as


m = (5)/(2)

Hope this helps you

User Asif Khan
by
5.5k points
5 votes

Answєr :


\Huge{\boxed{\sf{\red{m = (5)/(2)}}}}

Explαnαtion :


\displaystyle{\sf{ (3)/(2) + (2m)/(9) = (37)/(18)}}

| ∵ Transposing 3/2 to R.H.S


\implies
\displaystyle{\sf{ (2m)/(9) = (37)/(18) - (3)/(2)}}


\implies
\displaystyle{\sf{ (2m)/(9) = (37-27)/(18)}}


\implies
\displaystyle{\sf{ (2m)/(9) = (10)/(18) = (5)/(9)}}


\implies
\displaystyle{\sf{ 2m = (5)/(9) * 9}}


\implies
\displaystyle{\sf{ 2m = 5}}


\longrightarrow
\large{\boxed{\sf{\red{ m = (5)/(2)}}}}

User Stephen Curial
by
5.2k points